A critical review of the valuation processes of petrol filling stations in terms of the Municipal Property Rates Act 2004 - Margolius, Jerry (Department of Construction Economics and Management, 2016)
In 2004, the Municipal Property Rates Act 6 of 2004 (MPRA) was promulgated which repealed all the Valuation Ordinances that existed in South Africa. This introduced a single piece of legislation for the purposes of conducting municipal valuations. This study concentrated on the Cape Town Metropolitan 2006 General Valuation that, at the time, was the first local authority to conduct municipal valuations in terms of the new legislation. The research explored the extent to which local authorities intervened in the valuation process, the in dependent judgment of property valuers as well as non-co-operation by oil companies during the valuation process, which was evident by them not responding to the survey questions. The manner in which petrol filling stations were valued, the most frequently used methodology applied and the application of the MPRA in the process were explored. The research was supplemented with a survey of property valuers employed by the local authorities as well as in private practices. This culminated in a holistic overview of the shortcomings in the legislation, the methodology and practice by interested parties in arriving at the municipal valuation in order to provide a critical review. From the critical review, the shortcomings in the valuation processes were identified, the methodology was addressed and recommendations made to the local authority.